Analysis of factors influencing the amount of rice production in Banggai Regency - Evina, Ni Kadek; Lapian, Agnes L. Ch. P.; Siwu, Hanly F. Dj. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to find out how land area, workforce and capital influence rice production in Banggai Regency. Purposive sampling, which refers to the data source. This research uses a sampling method that considers certain factors. Examples were taken of up to forty participants. The type of information used in this research is primary data. Interviews with forty respondents produced direct primary data. Procedure Data analysis involved the use of multiple linear regression. The research results show that the volume of rice production in Banggai Regency is greatly influenced and profitable by land area. The impact of labor on output levels is small but positive for rice in Banggai Regency. The capital impact is negligible and detrimental to the level of rice production in Banggai Regency. The amount of rice production in Banggai Regency is greatly influenced by land area, labor and capital.